2019
DOI: 10.1002/casp.2428
|View full text |Cite
|
Sign up to set email alerts
|

Collective guilt, moral outrage, and support for helping the poor: A matter of system versus in‐group responsibility framing

Abstract: We examined how the framing of responsibility for reducing socio‐economic inequality affects individuals' emotional reactions towards the poor and the willingness to engage in prosocial actions. Attribution of responsibility to either the system (government and institutions), the less deprived in‐group, or the disadvantaged out‐group (poor) was measured (Study 1) and manipulated (Study 2). Consistent with our hypotheses, moral outrage was higher than collective guilt when system responsibility for inequalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
0
15
0
2
Order By: Relevance
“…This approach (i.e., the Social Identity Approach, see Hornsey, 2008 ) has been taken into account in theoretical and empirical studies on collective action (for a review of identities and collective action, see van Stekelenburg and Klandermans, 2007 ) and it continues to influence different models of this form of prosocial behavior. The influence of shared identities in different forms of collective participation has been studied as prerequisites ( Thomas et al, 2009 ), outcomes ( Páez et al, 2015 ) or both ( Drury and Reicher, 2005 ), and as moderators of several relationships in the literature (e.g., Shepherd et al, 2013 ; Krauth-Gruber and Bonnot, 2019 ).…”
Section: Stes Inclusive Identities and Collective Actionmentioning
confidence: 99%
“…This approach (i.e., the Social Identity Approach, see Hornsey, 2008 ) has been taken into account in theoretical and empirical studies on collective action (for a review of identities and collective action, see van Stekelenburg and Klandermans, 2007 ) and it continues to influence different models of this form of prosocial behavior. The influence of shared identities in different forms of collective participation has been studied as prerequisites ( Thomas et al, 2009 ), outcomes ( Páez et al, 2015 ) or both ( Drury and Reicher, 2005 ), and as moderators of several relationships in the literature (e.g., Shepherd et al, 2013 ; Krauth-Gruber and Bonnot, 2019 ).…”
Section: Stes Inclusive Identities and Collective Actionmentioning
confidence: 99%
“…Research linking group-based emotions and people's intention to take collective action to mitigate injustice have often found that moral outrage and collective guilt influence people's collective behavior (Krauth-Gruber & Bonnot, 2020). In the previous studies, scholars argued that people act when they feel a relevant group-based emotion (emotion-based route) and/or believe that they can achieve change (efficacy-based route) (Van Zomeren et al, 2004).…”
Section: Collective Action or Collective Behaviormentioning
confidence: 99%
“…Moral Outrage (MO): Expression of moral outrage entails putting responsibility on the system (Batson et al, 2007;Krauth-Gruber & Bonnot, 2020), especially on the government and the authorities responsible for providing justice and an equitable environment to the citizens. In this study, we coded moral outrage in the following ways:…”
Section: Coding Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even politicians who held economically liberal views remained very careful not to “question the principle of welfare” (Béland and Hansen, 2000 ). In a study conducted in France, participants -French university students- still rate the State as most responsible for reducing poverty (Krauth-Gruber and Bonnot, 2020 ), which suggests that the State is still credited with social prerogatives, at least among this sub-population.…”
Section: Introductionmentioning
confidence: 99%